Acute Hepatitis Induced by Intravesical BCG Therapy: A Rare but Serious Complication - Hakima Abid; Mouna Figuigui; Sidi Adil Ibrahimi; Mohamed El Abkari; Mohamed Mzyiene; Soufiane Ennaciri; Ouima Justin Ziba; Mohamed Jamal El Fassi; Layla Tahiri Elousrouti; Laila Chbani (Case Reports in Hepatology)
Bacillus Calmette and Guérin (BCG), widely used as a vaccination to prevent tuberculosis, is also used as immunotherapy, by intrabladder instillation, to treat superficial bladder cancers and prevent recurrence. Complications following instillation of BCG are most often localized reactions, such as cystitis or hematuria. They can more rarely be generalized and potentially severe such as hepatitis, pneumopathies, aortitis, and localization to hematopoietic tissue. We have reported the observation of a 47-year-old patient followed up for a bladder tumor operated for transurethral resection of the bladder, then having benefited from an instillation of BCG therapy complicated by occurrence a week later of an acute hepatitis. The diagnostic time was 2 days, and the outcome was favorable with corticosteroid therapy.